Pengembangan Media Pembelajaran Majalah Ilmu Alam Berbasis Moderasi Beragama pada Mata Pelajaran IPA di Kelas V SD/Mi - Ismail Ismail; Nur Asiah; Yudesta Erfaylian; Harjoni Harjoni (Journal on Education, 2024)
The background of this research is because, during the learning process in the classroom, most educators still teach using conventional methods, namely by using printed books so that many students feel bored. In the school environment, we don't only learn about learning materials, we are also required to learn about values important in social life, such as tolerance and respect for others in religious life or what we can call religious moderation. Therefore, media is needed that can attract students' interest while at the same time instilling the values of religious moderation, one of the media that can be used is magazines. In this case, researchers researching the development of magazines on natural science learning on the water cycle material used the ADDIE model which has several stages, namely analysis, design, development, implementation, and evaluation. Based on the analysis of the research results, it can be concluded that the development of learning media for natural science magazines based on religious moderation obtained an average score of 85% from material experts with very feasible criteria, an average of 90% from linguists with very feasible criteria, and an average of media experts 92% with very feasible criteria and declared feasible to be tested. In contrast, the average rating given by educators is 89% with a very feasible category to use. The assessment of students on a small scale is 89% and on a large scale gets 93% with a very decent category.